COLLECTIVE CRIBBING: MODEL OF PLAYERS' BEHAVIOUR IN TEAM - Mariya V. Kulabukhova; Olga A. Sokolova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
During one's life a person keeps on facing a dilemma: to attain a set goal by himself or to use team's assistance to make a task easier. A vivid example showing a complexity of choice in similar situation is a process of studying in university, when a student must decide whether he will crib or rely only on his own knowledge. Our research shows that decision-making in this case is affected not only by formal but also by informal institutes, such as friendship, principles of professional ethics, etc. Moreover, impact of informal institutional norms could become decisive during choosing an optimal strategy. The theoretical model and the experiment described in the article proved that in case certain personality characteristics are present independent work will be the most useful for the student.